Efforts of History Teachers in Developing Students’ Collaboration Skills at State Senior High School 5 Banjarmasin - Siti Maimuna; Herry Porda Nugroho Putro; Heri Susanto (STKIP Taman Siswa Bima, 2025)
This study focuses on the efforts of history teachers in developing collaboration skills among eleventh-grade students at SMA Negeri 5 Banjarmasin. The research background highlights the importance of 21st-century skills, particularly collaboration, which includes active contribution, responsibility, flexibility, productivity, and mutual respect. This study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing, while the validity of the findings was tested through technique and source triangulation. The results indicate that history teachers foster collaboration skills through the implementation of cooperative learning, project-based assignments, emphasis on social values, as well as mentoring and reflection activities. These strategies enabled students to contribute more actively, respect differing opinions, and enhance group responsibility. However, the study also found several challenges, such as the dominance of certain members, the passive attitude of some students, and limited instructional time. Overall, the research highlights the central role of teachers in facilitating collaboration skills, suggesting the need for innovative teaching approaches that align with the demands of the 21st century.